Impact of kidney transplantation in obese candidates: a time-dependent propensity score matching study. Issue 9 (19th April 2022) - Castelli, Christel; Foucher, Yohann; Boucquemont, Julie; Prezelin-Reydit, Mathilde; Giral, Magali; Savoye, Emilie; Hazzan, Marc; Lenain, Rémi
ABSTRACT: Background: Although kidney transplantation (KT) is considered the best treatment for end-stage renal disease (ESRD), there are concerns about its benefit in the obese population because of the increased incidence of post-transplant adverse events. We compared patients who underwent KT versus patients awaiting KT on dialysis. Methods: We estimated the life expectancy [restricted mean survival time (RMST)] for a 10-year follow-up by matching on time-dependent propensity scores. The primary outcome was time to death. Results: In patients with a body mass index (BMI) ≥30 kg/m 2 ( n = 2155 patients per arm), the RMST was 8.23 years [95% confidence interval (CI) 8.05–8.40] in the KT group versus 8.00 years (95% CI 7.82–8.18) in the awaiting KT group, a difference of 2.71 months (95% CI −0.19–5.63). In patients with a BMI ≥35 kg/m 2 ( n = 212 patients per arm), we reported no significant difference [8.56 years (95% CI 7.96–9.08) versus 8.66 (95% CI 8.10–9.17)]. Hence we deduced that KT in patients with a BMI between 30 and 35 kg/m 2 was beneficial in terms of life expectancy. Conclusion: Regarding the organ shortage, KT may be questionable for those with a BMI ≥35 kg/m 2 . These results do not mean that a BMI ≥35 kg/m 2 should be a barrier to KT, but it should be accounted for in allocation systems to better assign grafts and maximize the overall life expectancy of ESRD patients. Graphical Abstract: